Microblogging money: Exploring the world's central banks on Twitter - Iikka Korhonen; Elisa Newby; Jonna Elonen-Kulmala (Bank of Finland, 2024)
This article looks into global central bank messaging on the Twitter social media platform. At the end of 2021, a total of 122 central banks and monetary authorities had registered accounts on Twitter At that time, approximately two-thirds of world's central banks and monetary author- ities were using Twitter. Drawing on a database of central bank tweets up to the end of 2021, we document Twitter interactions of central banks by such measures as influence, connections and hashtag use. In addition to similarities among central bank strategies, we also find striking differences in influence and willingness to connect with the public. Tweeting activity during the Covid-19 pandemic provides insight in central bank crisis responses.
URN:NBN:fi-fe2024040515020
Keywords: E58; 330; central banks; communications; Twitter; Covid-19